Imaging endogenous HClO in atherosclerosis using a novel fast-response fluorescence probe. Issue 17 (4th February 2020) - Wang, Beibei; Zhang, Feng; Wang, Shukun; Yang, Ruijin; Chen, Chonghao; Zhao, Wei
Abstract : A novel probe S-ClO was developed, which could selectively sense HClO as well as monitor HClO-induced arterial vessel inflammation. Abstract : A novel pyrene-based naked-eye colorimetric and fluorescent turn-on probe (S-ClO ) was developed. Besides, imaging in living RAW264.7 cells, an arterial vessel inflammation nude mouse model and human serum using S-ClO indicates that S-ClO could serve as a potential tool for early diagnosing and monitoring inflammatory diseases.